A UNIQUE METHOD OF CARE OF UMBILICAL STUMP: INTERESTING SIMILARITY AMONG PRACTICES IN AFRICA AND ASIA - safiullah, Safiullah; Qureshi, Muhammad Salman H (Journal of Ayub Medical College Abbottabad, 2015)
Sepsis is an important cause of mortality in neonates Umbilicus is a common site for sepsis and requires utmost care in order to prevent probable risks of infection. There lies a difference in the method of cord cutting and caring the remaining stump of cord which varies from region to region based on the socio-cultural background.1 However, proper umbilicus care is very important to prevent chances of risk and infections. Different beliefs in different communities regarding cord care and handling of umbilicus exposes a newly born child to some potential dangerous consequences and risk for developing sepsis. A neonate presented to the Paediatric Ward of Kuwait Teaching Hospital, Peshawar, KPK with an umbilicus wrapped. The string was tied around his neck (refer to Figure 1) to apparently help in falling off the cord quickly as the baby moves his head. Handling umbilicus in such an unhygienic way is dangerous and can lead to bacterial infection and sepsis2, as was the case in this baby. It was really interesting to find that a similar practice also exist in Africa where the cord is held with string and then tied around the baby’s neck exclusively of male gender as the perception is that if the cord touches the genitalia then it will later cause sterility.3 It is therefore necessary to educate the parents of neonate to observe a proper protocol for the care of cord and umbilicus. This will not only help in minimizing risk of sepsis but also it will contribute in reducing unnecessary burden on neonatal health care centres and thus reducing yearly economic burden